Evaluation of Woof - A Tool For Developing a Prosperous School Class - Berdén,Signe; Mitic,Amanda (2023)
In order to deal with the rising stress levels of pupils, it is important to create a well-functioning learning environment. This can for example be done with various tools, one of them being Woof Technologies ApS platform WOOF which can be used as an aid for teachers in elementary school to measure and work with students' well-being in class. The purpose of this thesis is to analyze and evaluate Woof Technologies ApS platform WOOF from a usability perspective. Based on user-centered design, a heuristic evaluation was made on the existing program but also an exploratory investigation on the existing users of the program. Furthermore, through an iterative working method, two prototypes were created which underwent usability tests with observations and interviews. Based on the collected information, it was possible to compare the prototypes with each other and the existing program in order to draw conclusions about improvement opportunities to increase usability in the future, both short-term and long-term. The result showed that in the short term the platform would need, for example, more visual feedback, consistent language throughout the program, that cancel and back buttons are added, but also that the possibility to be able to navigate to the menu wherever the user is in the program is created. In addition, to simplify usability, collect everything that has to do with the same thing, for example, users on the same page. Long term, it is possible to add menu tabs in WOOF-space to divide the information, add a beginner's guide, but also information boxes that come up when you hover the mouse over, for example, buttons and icons. In addition, update the overview mode, adding a first page that shows all the graphs that exist to make it easier for the user to see the content.
Keywords: Usability; Prototype; Heuristic Evaluation; WOOF; Woof-space; User-centered design